Optimasi Void (Lubang Akhir Tambang) Pada Kegiatan Rencana Pascatambang Batubara di PT. Megaprima Persada Propinsi Kalimantan Timur: Void Optimization (Mining End Hole) in Coal Post Mining Plan Activities at PT. Megaprima Persada East Kalimantan Province - Rifandy, Akhmad (Media Ilmiah Teknik Lingkungan (MITL), 2023)
This study aims to optimize the void function by engineering material handling so that in the post-mining stage it is expected that Void in the Northern area of 40 Ha with drainage RL 20 and Void in the Southern area of 140 Ha with drainage RL 11 to be used as a source of irrigation for rice fields and become the location of the planned infrastructure development of Solar Power Plants. Descriptive and quantitative data analysis is assisted using Geovia Minex, X Pac, Autocad Land Desktop, and Microsoft Excel software. Void optimization efforts yield; in the North void, the amount of material to be moved is 1,048,905 LCM, and the South void requires 2,346,460 LCM so the total volume of OB needed is 3,395,365 LCM. The work time is 15 months (1 year 3 months) using the main tool 3 units of PC 400 for excavation and 9 units of HINO FM260 for transportation with a total required cost of US 7,630,777